Measurement of the Λb0 lifetime using semileptonic decays - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We report a measurement of the Λb0 lifetime using a sample corresponding to 1.3fb-1 of data collected by the D0 experiment in 2002-2006 during run II of the Fermilab Tevatron collider. The Λb0 baryon is reconstructed via the decay Λb0→μν̄Λc+X. Using 4437±329 signal candidates, we measure the Λb0 lifetime to be τ(Λb0)=1.290-0.110+0.119(stat)-0.091+0.087(syst)ps, which is among the most precise measurements in semileptonic Λb0 decays. This result is in good agreement with the world average value. © 2007 The American Physical Society.